Assessing the Quality of Diabetic Patients Care - Belkis Vicente Sánchez; Elodia Rivas Alpízar; Gisela Zerquera Trujillo; Dania Peraza Alejo; Innerys Rosell García (Revista Finlay)
Background: to improve the efficiency and effectiveness of the actions of family doctors and nurses in this area is an indispensable requisite in order to achieve a comprehensive health care. Objective: to assess the quality of health care provided to diabetic patients by the family doctor in Abreus health area. Methods: a descriptive and observational study based on the application of tools to assess the performance of family doctors in the treatment of diabetes mellitus in the five family doctors consultation in Abreus health area from January to July 2011 was conducted. The five doctors working in these consultations, as well as the 172 diabetic patients were included in the study. At the same time, 172 randomly selected medical records were also revised. Through observation, the existence of some necessary material resources and the quality of their performance as well as the quality of medical records were evaluated. Patient criteria served to assess the quality of the health care provided. Results: scientific and technical training on diabetes mellitus has been insufficient; the necessary equipment for the appropriate care and monitoring of patients with diabetes is available; in 2.9% of medical records reviewed, interrogation appears in its complete form including the complete physical examination in 12 of them and the complete medical indications in 26. Conclusions: the quality of comprehensive medical care to diabetic patients included in the study is compromised. Doctors interviewed recognized the need to be trained in the diagnosis and treatment of diabetes in order to improve their professional performance and enhance the quality of the health care provided to these patients.